2015
DOI: 10.1186/s12967-015-0554-5
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine ameliorates acute lung injury following orthotopic autologous liver transplantation in rats probably by inhibiting Toll-like receptor 4–nuclear factor kappa B signaling

Abstract: BackgroundTo investigate whether pretreatment with dexmedetomidine (Dex) has a protective effect against acute lung injury (ALI) in an orthotopic autologous liver transplantation (OALT) rat model and to explore the mechanisms responsible for the protective effect of Dex against lung injury.MethodsForty-eight rats underwent OALT and were randomly divided into six groups (n = 8 in each group) that received 10 µg/kg Dex, 50 µg/kg Dex, 50 µg/kg Dex + nonspecific α2-adrenergic receptor (AR) antagonist atipamezole, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…In correspondence with previous electronmicroscopic and functional studies (Aoki et al, 1998;Hutchinson et al, 2011), we also found immunopositive staining in reactive astrocytes in the lesioned regions, which was most prominent during the 1 st month after post-TBI. This led us to investigate whether ATI affects the release of inflammatory cytokines, as suggested by previous studies in models of brain, lung, and kidney injury (Chi et al, 2015;Yao et al, 2015;Ren et al, 2016). Moreover, whether the alleviation of inflammation-related odema by ATI could explain some of the enhanced somatomotor recovery.…”
Section: Target Expression and Mechanisms Of Action Of Atimentioning
confidence: 86%
“…In correspondence with previous electronmicroscopic and functional studies (Aoki et al, 1998;Hutchinson et al, 2011), we also found immunopositive staining in reactive astrocytes in the lesioned regions, which was most prominent during the 1 st month after post-TBI. This led us to investigate whether ATI affects the release of inflammatory cytokines, as suggested by previous studies in models of brain, lung, and kidney injury (Chi et al, 2015;Yao et al, 2015;Ren et al, 2016). Moreover, whether the alleviation of inflammation-related odema by ATI could explain some of the enhanced somatomotor recovery.…”
Section: Target Expression and Mechanisms Of Action Of Atimentioning
confidence: 86%
“…In our study, we demonstrated that the limb I/R‐induced remote overexpression of TNF‐α, IL‐1, and IL‐6 in the lungs was attenuated by DEX preadministration. Previous studies demonstrated that DEX lowered mortality, reduced pulmonary inflammation, and inhibited TLR4/MyD88 expression and NF‐κB activation in the lung tissues of septic rats . DEX pretreatment downregulated TLR4 and NF‐κB proteins in the liver and inhibited the release of the pro‐inflammatory cytokines TNF‐α and IL‐1β in the serum .…”
Section: Discussionmentioning
confidence: 96%
“… Rats in the M group (model group, established OALT model) underwent OALT operation including portal vein (PV) and inferior vena cava (IVC) occlusion for 20 minutes, followed by reperfusion for eight hours. Based on the previous studies 48 49 50 , rats in the D1 group (10 μg/kg of Dex + OALT group) received 10 μg/kg of Dex injected intraperitoneally (i.p.) 30 minutes prior to OALT.…”
Section: Methodsmentioning
confidence: 99%